2016
DOI: 10.1093/iwc/iww003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three QWERTY Keyboards for a Smartwatch

Abstract: The QWERTY keyboard has been a de facto standard for computer text entry and continues to be one for mobile text entry such as for smartphones. It is not clear, however, that it will continue to be an option for text entry for much smaller devices such as smartwatches. In a series of user experiments, we examined the performance of the QWERTY keyboard when it is reduced to fit a small smartwatch screen. At the same time, we examined whether the ZoomBoard and the SplitBoard, which are QWERTY keyboards augmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Additionally, all three studies found typing performance significantly worsened while walking than when standing, as it does on a smartphone. Hong et al (2016) and Darbar et al (2016) reported typing speeds ranging from 8 to 15 WPM when walking or standing with alternative keyboards and 5 to 13 WPM with a standard QWERTY keyboard using tap input. Turner et al (2018) reported typing speeds of 35 WPM with trace and 30 WPM with tap using a standard QWERTY keyboard when walking or standing.…”
Section: Walking and Typing On A Smartwatchmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, all three studies found typing performance significantly worsened while walking than when standing, as it does on a smartphone. Hong et al (2016) and Darbar et al (2016) reported typing speeds ranging from 8 to 15 WPM when walking or standing with alternative keyboards and 5 to 13 WPM with a standard QWERTY keyboard using tap input. Turner et al (2018) reported typing speeds of 35 WPM with trace and 30 WPM with tap using a standard QWERTY keyboard when walking or standing.…”
Section: Walking and Typing On A Smartwatchmentioning
confidence: 99%
“…However, the walking scenarios employed in each study varied. Hong et al (2016) and Turner et al (2018) simulated the walking task using a treadmill. Darbar et al (2016) had participants perform a naturalistic walking scenario, but the details of the walking scenario were not provided.…”
Section: Walking and Typing On A Smartwatchmentioning
confidence: 99%
See 1 more Smart Citation
“…Both objective and subjective data were taken from the participants. We learned that similar measurements were successfully employed for comparing several keyboard layouts, such as in [35] for accuracy and typing speed of linear QWERTY keyboard layouts, in [36] for relative error rate of a smartwatch keyboard layout, and in [40] for typing speed, error rate, and learning time of Bangla keyboard layouts. However, the different contexts and limitations of resources caused some variations in the detailed formula and application of those measurements.…”
Section: Usability Evaluation Of Keyboard Layoutsmentioning
confidence: 99%
“…An important aspect of keyboards is the keyboard layout, that is any specific arrangement of the keys, legends, or key-meaning associations (respectively) of a computer keyboard [8]. This arrangement can be mechanical/physical [9] [10], visual [9], or functional/logical [9] [11]. The mechanical/physical layout is the placements of keys of a keyboard [9] [10].…”
Section: Introductionmentioning
confidence: 99%